Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.17221/82/2016-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

The effect of copper on plant regeneration in barley microspore culture

Abstract: Makowska K., Oleszczuk S., Zimny J. (2017): The effect of copper on plant regeneration in barley microspore culture. Czech J. Genet. Plant Breed., 53: 17-22.Isolated microspore culture is an excellent system for the production of doubled haploids in many crops, including barley. In a more traditional barley anther culture method copper sulphate is known to enhance plant regeneration. Here we report that one hundred times higher concentration of copper sulphate in the isolated microspore culture of two spring b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
1
14
0
1
Order By: Relevance
“…AGPs have not been noted as involved in plastid development so the absence of an effect on albinism was not unexpected. This also provides further evidence that the development of embryos converting into the plants and chloroplast biogenesis during androgenesis are two independent processes (Chaudhary et al 2003;Makowska et al 2017).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…AGPs have not been noted as involved in plastid development so the absence of an effect on albinism was not unexpected. This also provides further evidence that the development of embryos converting into the plants and chloroplast biogenesis during androgenesis are two independent processes (Chaudhary et al 2003;Makowska et al 2017).…”
Section: Discussionmentioning
confidence: 56%
“…Both have high androgenic potential but with a rather low level of plant regeneration and high proportion of APs (Makowska et al 2017). Seeds were germinated on moistened filter paper in Petri dishes for 5 days at 4 °C and then for 7 days at 16 °C in the dark.…”
Section: Plant Materialsmentioning
confidence: 99%
“…The caryopses were sterilized by soaking in 70% ethanol for 1 min, followed by stirring in 10% sodium hypochlorite for 20 min. The sterilized caryopses were rinsed several times with sterile water ( Makowska et al, 2017 ) and used for immature zygotic embryo extraction. The extracted immature zygotic embryos were placed in Petri dishes (60 × 15 mm) containing solid N6L medium comprising macro- and micronutrients ( Chu, 1978 ) and supplemented with 2 mg l –1 2,4-dichlorophenoxyacetic acid (2,4-D), 0.5 mg l –1 6-naphthalene acetic acid (NAA), and 0.5 mg l –1 kinetin.…”
Section: Methodsmentioning
confidence: 99%
“…As explants cultured using both protocols were incubated in the same types of culture vessels and the same tissue culture chamber, our evidence of the WU protocol being more promotive of albino regeneration suggested that medium composition played a role in this response. Previous studies have shown that inclusion of casein hydrolysate reduced albinism during in vitro regeneration [66], while the use of maltose as a carbohydrate source [64], TDZ as a cytokinin source [72] and copper supplements [73] promoted albinism. While the WU protocol was more supportive of overall plantlet regeneration than LG, this protocol contained almost 8-fold higher levels of copper sulfate in both CIM and RM formulations, as well as the use of maltose in CIM, and TDZ in RM.…”
Section: Albino Regenerationmentioning
confidence: 99%